The intersection of promotion policies, research habitus, and capital distribution: a qualitative case study of two higher education contexts in the United Arab Emirates - Elhakim, Ahmed (Frontiers in Education, 2024)
Career advancement must be based on merit, according to the universal norm. However, faculty members continue to express their dissatisfaction with the existing promotion policies and practices, highlighting issues like ambiguity, lack of transparency, inconsistent implementation, and the overall fairness of the evaluation process. This study aimed to explore the intersections of promotion policies with the research habitus and the distribution of different forms of capital in two higher education institutes in the United Arab Emirates. Data were gathered from a purposively selected sample of faculty members using semi-structured interviews in addition to key policy documents at both institutes. Using Bourdieu's notion of habitus, capital, and field, the study identified key characteristics of the research habitus and how it shapes perceptions towards aspects of competitiveness and collegiality as practiced in the research world. The study also examined potential relationships between research habits and promotion policies. Finally, the study explored capital distribution in the research field and identified some of the undisclosed aspects of the promotion world, highlighting areas like prior education, affiliations, professional experience, cultural background, ethnicity, and social networks as some of the factors that may play a role in the promotion outcomes. The findings of the study can be used to offer an additional layer of understanding some hidden rules of academic research fields and capital distribution in light of institutional policy development and enactment. Such understanding can be used to make recommendations on how existing challenges can be addressed to improve perceptions of the clarity and fairness of faculty promotion policies and encourage more transparent practices.